The nurse’s point of view in the intensive care unit in relation to cancer patients - Fabiani Barros Moura de Vasconcelos, Ana Carolina Floriano de Moura, Fernanda Claúdia Miranda Amorim, Daniel Coelho Farias, Neylany Raquel Ferreira da Silva, Mayra Borges Macedo6 (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v3i2.1214